RESOLUTION OF ISLAMIC EDUCATION CLUSTER TEACHERS ON THE CHALLENGES OF ISLAMIC EDUCATION IN GLOBALIZATION ERA - Ahmad Abdul Rochim (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
This research aims to identify the challenges faced by Islamic education cluster teachers in teaching Islamic education in the era of globalization, the factors causing constraints or challenges in Islamic education in this era, and aims to understand how Islamic education cluster teachers overcome challenges in Islamic education in the era of globalization. The research method used in this study is field research or case studies, utilizing observation, interviews, and documentation techniques for data collection. Data validity is tested through credibility, transferability, dependability, and confirmability. Data analysis is conducted through data collection, reduction, presentation, and conclusion drawing. The results show that the changing times have an impact on education, including teaching Islamic education especially at MA Negeri 5 Cirebon. Therefore, resolutions from teachers, especially Islamic education cluster teachers, are crucial in addressing these issues. It can be concluded that the resolutions of Islamic education cluster teachers on the challenges of Islamic education in the era of globalization at MA Negeri 5 Cirebon, Cirebon Regency, have been well implemented and have received positive responses from students. As for the novelty in this research, there is a resolution from Islamic education cluster teachers on the challenges of globalization era. Thus, this finding indicates that with the resolution of Islamic education cluster teachers, it is a planning step or a change action in carrying out the education process, especially Islamic education, so that it can proceed effectively.